Multidimensional analysis of relevance. Case study of an intervention model with a differential approach - Rincón, Gustavo (2020)
The academic literature has demonstrated the relevance of education not only on the economic development of society but also on the human and cultural development of individuals. That is why, one of the main challenges of governments is the access of individuals of different population groups to education and its quality, the search for the relevant sea according to the economic, historical, social and cultural context. In this sense, this document seeks to analyze the relevance of some training programs offered under an intervention model focused on the population, based on the set of factors important for the development of the individual and society, implemented a multidimensional approach that includes the educational-pedagogical, the social in conjunction with social and cultural equity, finally, the economic, institutional and political. This analysis is complemented by the description of the behavior of the apprentices, specific in their cooperative attitudes and integral biases, based on the application of experimental and behavioral economics techniques.